Pembinaan Sistem Akuntansi Dalam Pengelolaan Ukm Kampung Boneka - Kaca Dian Meila; Elok Faiqoh Himmah (Jurnal Bhakti Karya dan Inovatif, 2022)
At The end of 2019, the world was shocked by the Covid-19 which had an impact of the economy in the word especially for Small and Medium Enterprise Business in Indonesia. Based on data, there are 949 reports from Small and Medium Enterprise Business had impact from Covid-19 (Kompas, 27 Maret 2020). The Small and Medium Enterprise is one of the business that greay demand by the people in Indonesia. ). The Small and Medium Enterprise come from all variant public. The product offered are also diverse. The number of business people is also increasing every year. The Small and Medium Enterprise Business are also able to opportunities a new job for other people. So, it’s very reasonable if the Small and Medium Enterprise is growing day by day and the people are excited for it. This business is also a concern the government because The Small and Medium Enterprise can give a big impact on the economy sector in the country. In fact, The Small and Medium Business people have a difficulty in carrying out their business activities because one of the impacts Covid-19 is a decrease in people purchasing power which impact to The Small and Medium Business a decrease in sales. So that, The Small and Medium Business must be able to go digital marketing product that is right on target in order to increase sales in pandemic Covid-19. This problem occurs in the Small and Medium Business at Doll Village in Kopo Sayati, Bandung Regency. We can help the problem in the Small and Medium Business at Doll Village, we can as a lecture in accounting department and as a form of college Tridharma, so we provide a coaching about the managing finances are good, planning a sales target during the pandemic Covid-19, apply the digital marketing product so had a impact increase online sales that can be accepted by the public.